2016
DOI: 10.1007/s10997-015-9339-8
|View full text |Cite
|
Sign up to set email alerts
|

Conflict in the boardroom: a participant observation study of supervisory board dynamics

Abstract: We develop a conflict-oriented model of board task performance and argue that a common framework, that is, a shared understanding of its role, helps boards to perform well. Conflict is the mediating effect through which this plays out. We posit that a common framework increases board task performance because it reduces intragroup relationship conflicts, increases task conflicts within the board, and reduces conflicts in the relationship between board and CEO. We explore the model through a comparative particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 96 publications
3
45
0
3
Order By: Relevance
“…Minichilli et al (2012) also found no direct meaningful relationship between cognitive conflict and board effectiveness, pointing at a common unwillingness of boards to engage in frank and open discussion. Heemskerk, Heemskerk and Wats (2015), in their participant observation study of 11 Dutch supervisory boards, found that although high cognitive (task) conflict can be positive for board effectiveness, it can also bring about affective (relationship) conflict, which can decrease board effectiveness. This interaction may explain part of the empirical and theoretical confusion.…”
Section: Board Processesmentioning
confidence: 99%
“…Minichilli et al (2012) also found no direct meaningful relationship between cognitive conflict and board effectiveness, pointing at a common unwillingness of boards to engage in frank and open discussion. Heemskerk, Heemskerk and Wats (2015), in their participant observation study of 11 Dutch supervisory boards, found that although high cognitive (task) conflict can be positive for board effectiveness, it can also bring about affective (relationship) conflict, which can decrease board effectiveness. This interaction may explain part of the empirical and theoretical confusion.…”
Section: Board Processesmentioning
confidence: 99%
“…The Board should therefore incorporate actions of social and environmental concerns in defining business and operations, covering the sustainable management of companies. Furthermore, they should develop rules to enhance the diagnosis and counseling of higher management in decision making, working as consultative bodies (Heemskerk, Heemskerk, & Wats, 2016;IBGC, 2009b;Oliva & Albuquerque, 2006).…”
Section: Board Committeesmentioning
confidence: 99%
“…Contextual. Esta corrente considera a influência das contingências e perspectivas dos múltiplos stakeholders sobre os conselhos, examinando como a atuação do órgão depende do contexto em que a empresa está envolvida (Heemskerk et al, 2017;Minichilli, Zattoni, Nielson, & Huse, 2012;Pugliese et al, 2014). Os estudos contextuais observam a governança corporativa em um ambiente institucional e social amplo, em que o poder do conselho é relativo e depende de diversos fatores, como o setor em que a empresa atua, o desenvolvimento das relações entre as várias coalizões internas e externas com interesse na empresa, os regramentos legais, entre outros (Aguilera, Filatotchev, Gospel, & Jackson, 2008).…”
Section: Foco Contingencialunclassified
“…Algumas pesquisas têm tentado atender a esse chamado ao explorarem os processos inerentes às atividades dos conselhos e os seus diferentes papéis (Heemskerk, Heemskerk, & Wats, 2017;Minichilli et al, 2009;Nicholson & Kiel, 2004;Pugliese, Minichilli, & Zattoni, 2014;Wan & Ong, 2005;Zattoni et al, 2015). Essa visão se baseia no fato de que os conselhos podem ser caracterizados como grupos que tomam decisões complexas, porém esporádicas.…”
Section: Introductionunclassified
See 1 more Smart Citation